2015
DOI: 10.1155/2015/469147
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Claims and Their Authenticity in Indian Drug Promotional Advertisements

Abstract: Introduction. Drug promotional advertisements (DPAs) form a major marketing technique of pharmaceutical companies for promoting their products and disseminating ambiguous drug information which can affect prescribing pattern of physicians. Drug information includes product characteristics, various marketing claims with references in support to increase its credibility and authenticity. Material and Methods. An observational study was carried out on fifty printed drug advertisement brochures which were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
5
16
0
Order By: Relevance
“…This unethical advertisement of drugs highlighting the positives, built misconceptions and encourages drug consumerism and contributing to irrational drug use through inappropriate prescribing. 5 Several claims regarding efficacy, safety, convenience, pharmacokinetic property and cost were observed to be quite common in our study which are in line with the findings of a similar study conducted by Mali et al in a tertiary care hospital. 10 A total of 339 claims were made in our study ranging from 1-6 per DPL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This unethical advertisement of drugs highlighting the positives, built misconceptions and encourages drug consumerism and contributing to irrational drug use through inappropriate prescribing. 5 Several claims regarding efficacy, safety, convenience, pharmacokinetic property and cost were observed to be quite common in our study which are in line with the findings of a similar study conducted by Mali et al in a tertiary care hospital. 10 A total of 339 claims were made in our study ranging from 1-6 per DPL.…”
Section: Discussionsupporting
confidence: 92%
“…3 Various studies have demonstrated that printed drug promotional materials distributed by the pharmaceutical companies are often biased. 4,5 Lack of time to access medical literature further complicate the way in to impartial drug information in developing countries. 6 In today's era, with the discovery of newer generations of therapeutic agents, prescribing physicians need to keep themselves updated with the ever changing scientific knowledge of medicines.…”
mentioning
confidence: 99%
“…Few DPLs did mention about these but it was in a very small font that could be read with difficulty which is unethical. The ratio of number of references to number of claims was not appropriate, similar observations were made in the study by Randhawa, et al 12 Only 46% of the DPLs had a complete address, same as quoted in the study by Nath S et al, which makes the traceability of the manufacturer a difficult task. 13 None of them mentioned about over dosage and other ingredients known to cause problems.…”
Section: Discussionmentioning
confidence: 70%
“…They form the major marketing techniques. 5 Due to the concise nature of DPLs, busy medical practitioners may sometimes rely on them as the primary source of drug information. They can be highly informative when it provides the authentic information in a nutshell as long as they have been critically analysed and reviewed if not, they can be misleading.…”
mentioning
confidence: 99%